Pertanggungjawaban Pelaku Tindak Pidana Kekerasan Seksual di Provinsi Aceh Ditinjau dari Hukum Pidana Nasional dan Qanun Aceh Nomor 6 Tahun 2014 Tentang Hukum Jinayat - Celsa Madila, Dekia; Farrih Izadi, Fariz (Bandung Conference Series: Law Studies, 2024)
Abstract. Sexual violence is a form of crime that insults and tarnishes human dignity. The national criminal law regulates provisions regarding sexual violence in Law Number 12 of 2022 with 9 (nine) types of sexual violence. The Qanun Jinayat regulates 2 (two) types of sexual violence. The formulation of the problem in this research includes: What are the differences in the types of criminal acts of sexual violence in the national criminal law and Aceh Qanun Number 6 of 2014 concerning Jinayat Law and what forms of accountability exist for perpetrators of sexual violence crimes in terms of the national criminal law and Aceh Qanun Number 6 of 2014 concerning Jinayat Law. The goal is to find out what has been described in the formula. The research method used is a normative juridical method with a qualitative approach. The results of this research are Law no. 12 of 2022 accommodates 9 (nine) types of sexual violence with levels of punishment that depend on the consequences obtained by the victim. Meanwhile, Qanun Jinayat is only limited to regulating sexual harassment and rape, the elements of which are in harmony with those in Islamic law. Regarding the form of accountability for perpetrators of sexual violence, the national criminal law and Qanun Jinayat have differences in the objectives of the punishment. Abstrak. Kekerasan seksual merupakan suatu bentuk kejahatan yang melecehkan dan menodai harkat kemanusiaan. Hukum pidana nasional mengatur ketentuan mengenai kekerasan seksual dalam Undang – Undang Nomor 12 Tahun 2022 dengan 9 (sembilan) jenis kekerasan seksual. Adapun Qanun Jinayat mengatur 2 (dua) jenis kekerasan seksual. Rumusan masalah dalam penelitian ini meliputi: Bagaimana perbedaan jenis tindak pidana kekerasan seksual dalam hukum pidana nasional dan Qanun Aceh Nomor 6 Tahun 2014 tentang Hukum Jinayat serta Bagaimana bentuk pertanggungjawaban pelaku tindak pidana kekerasan seksual ditinjau dari hukum pidana nasional dan Qanun Aceh Nomor 6 Tahun 2014 tentang Hukum Jinayat. Tujuannya adalah untuk mengetahui apa yang telah diuraikan pada rumusan tersebut. Metode penelitian yang digunakan adalah metode yuridis normatif dengan pendekatan kualitatif. Hasil dari penelitian ini yaitu Undang – Undang No. 12 Tahun 2022 mengakomodir 9 (sembilan) jenis kekerasan seksual dengan kadar hukuman yang bergantung pada akibat yang didapat oleh korban. Sedangkan, Qanun Jinayat hanya terbatas mengatur jarimah pelecehan seksual dan pemerkosaan yang mana unsur – unsurnya memiliki keselarasan dengan yang ada dalam syari’at Islam. Adapun mengenai bentuk pertanggungjawaban pelaku kekerasan seksual dari hukum pidana nasional dan Qanun Jinayat memiliki perbedaan dalam tujuan pemidanaanya.